The role of early social motivation in explaining variability in functional language in toddlers with autism spectrum disorder. (January 2021) - Su, Pumpki L; Rogers, Sally J; Estes, Annette; Yoder, Paul
This study examined an insufficiently studied predictor of functional language, social motivation, in a group of 87 young children with autism spectrum disorder. Participants (age 14–31 months at the start of the study) were assessed at four times over 24 months. We tested total and indirect associations between early social motivation and later expressive language to understand the behavioral mechanisms by which social motivation might affect functional language development. Results from this study show that early social motivation predicts functional language 2 years later in young children with autism spectrum disorder. In addition, this positive longitudinal association is serially mediated by intentional communication and then receptive language. These findings are consistent with the elicited bootstrapping hypothesis which proposes that children with relatively stronger social motivation produce more intentional communication. This, in turn, elicits others' linguistic input which impels receptive language development. This process eventually results in relatively increased expressive language development. Lay abstract: About one-third of children with autism spectrum disorder never develop the language that they need in different day-to-day situations. Identifying potential factors that can predict later language development is crucial to understanding why some children with autism spectrum disorder successfully develop language while others do not. This study sought to investigate one of the understudied predictors of language development, social motivation, and to test theories for why this association may occur. Testing the theories requires that we measure children's ability to deliberately and directly communicate with others (i.e. intentional communication) and children's language understanding between the measures of social motivation and later expressive language. We tested 87 children with autism spectrum disorder, aged 14–31 months, at four times over 24 months. We found that children with relatively stronger social motivation had relatively better language use 2 years later. This positive link was partly due to a child's ability to produce intentional communication and to understand language. Although we did not measure parents' talking to their children, a theory that inspired this study suggests that children who use frequent intentional communication probably motivate others to talk with them frequently, which facilitates children's language understanding which leads to the development of expressive language. This theory, if confirmed to be true, can provide guidance for parents who want to help their children learn to talk. Parents could look for intentional communication from their children and respond by talking to their children. Effective intervention on both parent and child targets will likely enhance treatment efficacy. Future work is needed to test these ideas.